Functionality of two canopy bridge designs: successful trials for the endangered black lion tamarin and other arboreal species - Garcia, Francini de Oliveira; Culot, Laurence [UNESP]; de Carvalho, Rafaela Endrika Wolf Ferreira [UNESP]; Rocha, Vlamir José (Springer Nature, 2022)
Canopy bridges are crossing structures specific to mitigate the impact of roads on arboreal animals. Long-term monitoring of such infrastructures together with the analysis of design preferences has never been done in South America. To avoid the roadkills of a threatened primate species, the black lion tamarin (Leontopithecus chrysopygus), in Guareí, São Paulo, Brazil, we installed two designs of canopy bridges: a wood pole bridge and a rope bridge. We aimed to (1) evaluate the functionality (number of species and events) of both designs, (2) test the design preference of each species, and (3) determine if there were seasonal differences in the use of canopy bridges. We monitored the canopy bridges continuously since their installation with camera traps during 3 years. We recorded nine mammal and one lizard species crossing on the canopy bridges as well as 13 bird species using them as perches. Overall, the probability of crossing was higher on the wood pole bridge and the number of crossings, considering both designs, was higher during the dry season. One lizard and seven mammal species used the wood pole bridge, including the black lion tamarin, and six mammal species used the rope bridge. Four out of five species tested, including the black lion tamarin, preferred the wood pole bridge. While replications of this experimental design are necessary to obtain a more robust evaluation of the effectiveness of these canopy bridges, our study suggests that wood pole bridges might be an effective tool to reduce roadkills of the endangered black lion tamarin and possibly other arboreal species.
Keywords: Camera trap; Monitoring; Neotropical primate; Road mitigation; Roadkill; Wildlife crossing structures